Distributed serverless architectures on AWS : design and implement serverless architectures - Paul, Jithin Jude (Apress, 2023)
Explore the serverless world using Amazon Web Services (AWS) and develop various architectures, including those for event-driven and disaster recovery designs. This book will give you an understanding of different distributed serverless architectures and how to build them using AWS components. You will begin with an introduction to serverless components and architectures, before progressing to data platforms and containers. Next, you'll dig deeper into these serverless architectures and how they leverage AWS components through practical use cases. You will also explore designing systems in a multi-cloud paradigm. Author Jithin Jude Paul then demonstrates how efficient serverless architectures are, and the benefits of designing distributed systems globally in a cost-effective way while incorporating a microservices architectural style. Distributed Serverless Architectures with AWS concludes with a discussion of current and future trends in serverless frameworks. After completing this book, you'll be able to design distributed serverless architectures using AWS. You will: Gain an overview of different serverless architectures Design and build distributed systems using serverless components Build serverless data and container platforms on AWS Plan a multi-cloud strategy using serverless components.